ARGENTINA FOREIGN POLICY ON BIOFUELS IN PERSPECTIVE - Cristian Lorenzo (Revista Conjuntura Austral, 2012)
This article focus on Argentina foreign policy on biofuels in 2008 Food and Agricultural United Nations (FAO) Conference. To do this, we examinated during 2004-2008 its international historical context and FAO financial system, both as structures.